A digitally controlled model of an active ultrasonic transducer matrix for projection imaging of biological media - Krzysztof J. OPIELIŃSKI; Tadeusz GUDRA; Piotr PRUCHNICKI (Archives of Acoustics)
The following work presents the idea of constructing a digitally controlled active piezoceramic transducer matrix for ultrasonic projection imaging of biological media in a similar way as in case of roentgenography (RTG). Multielement ultrasonic probes in the form of flat matrices of elementary piezoceramic transducers require attaching a large number of electrodes in order to activate the individual transducers. This paper presents the idea of minimising the number of transducer connections in an active row-column matrix system. This idea was verified by designing a model of a matrix consisting of 16 ultrasonic transducers with electrode attachments optimised by means of electronic switches in rows and columns and miniature transistor switches in the nodes of the matrix allowing to activate selected transducers. The results of measurements and simulations of parameters of the designed matrix show that it is suitable to be used in projection imaging of biological media as a sending probe. In to use the matrix as a universal sending or receiving probe, it was suggested to add further switches that would eliminate the undesired effect of crosstalks in case of switches used for toggling the transducers in the nodes of the matrix.